1997
DOI: 10.1097/00042560-199703010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy and Zidovudine Therapy on Viral Load in HIV-1-Infected Women

Abstract: The objective of this study was to determine the effect of pregnancy and zidovudine (ZDV) on viral load in HIV-1 infected women. A prospective nonrandomized cohort study was conducted at a university medical center and affiliated clinic and included 44 HIV-1-seropositive pregnant women seen between June 1991 and September 1995. Twenty-three women initiated ZDV therapy during their pregnancy. Seventeen women did not take antiretrovirals, and four women took ZDV prior to and throughout pregnancy. HIV-1 viral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…Because ZDV therapy has little effect on maternal virus levels and ZDV is effective in reducing transmission regardless of the maternal HIV-1 RNA copy number in plasma, it is believed that a significant portion of the protection is due to chemoprophylaxis in the newborn following exposure to the virus, rather than to a reduction of virus levels in the maternal blood (3,12,27,28,38). Further evidence for this chemoprophylactic mechanism was provided by a recent study in Uganda which demonstrated that the rate of perinatal HIV transmission was greatly reduced by administration of two doses of nevirapine, the first given to the mother in labor and the second given to the infant shortly after birth (16).…”
Section: Simian Immunodeficiency Virus (Siv) Infection Of Newborn Macmentioning
confidence: 99%
“…Because ZDV therapy has little effect on maternal virus levels and ZDV is effective in reducing transmission regardless of the maternal HIV-1 RNA copy number in plasma, it is believed that a significant portion of the protection is due to chemoprophylaxis in the newborn following exposure to the virus, rather than to a reduction of virus levels in the maternal blood (3,12,27,28,38). Further evidence for this chemoprophylactic mechanism was provided by a recent study in Uganda which demonstrated that the rate of perinatal HIV transmission was greatly reduced by administration of two doses of nevirapine, the first given to the mother in labor and the second given to the infant shortly after birth (16).…”
Section: Simian Immunodeficiency Virus (Siv) Infection Of Newborn Macmentioning
confidence: 99%
“…First, in a retrospective study of HIV-infected women who discontinued ARVs at delivery (Tungsiripat et al 2007), median VLs at 12-96 weeks PP were similar to values obtained during pregnancy. In another study of 44 HIV-infected pregnant women, 23 women initiated ZDV therapy during pregnancy, 17 women did not use ARVs and four women used ZDV before and during pregnancy (Melvin et al 1997). Overall, VLs remained stable until six weeks PP, but there was a trend toward an increase in VL values PP among those women who received ZDV therapy only during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, other studies have assessed VL changes among HIV-infected women according to the continuation or discontinuation of ARVs after delivery (Cao et al 1997, Melvin et al 1997, Watts et al 2003, Martin et al 2006, Tungsiripat et al 2007. Some studies have suggested no change in VL PP, although others indicated VL increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating HIV-infected pregnant women with the antiretroviral drug zidovudine was associated with a reduced rate of transmission (Connor et al, 1994), though the drug may not produce this effect by reducing viral load: a recent study found that zidovudine reduced vertical transmission despite a minimal effect on viral load (Melvin et al, 1997;Newberry and Kelsey, 2003). Whatever the mechanism of zidovudine, it remains generally true that risk of vertical transmission can be minimized if therapies known to reduce the patient's serum and vaginal viral loads are continued during pregnancy.…”
Section: Maternal Viral Load and Vertical Hiv Transmissionmentioning
confidence: 99%